2013
DOI: 10.1186/1471-2105-14-349
|View full text |Cite
|
Sign up to set email alerts
|

MosaicIA: an ImageJ/Fiji plugin for spatial pattern and interaction analysis

Abstract: BackgroundAnalyzing spatial distributions of objects in images is a fundamental task in many biological studies. The relative arrangement of a set of objects with respect to another set of objects contains information about potential interactions between the two sets of objects. If they do not “feel” each other’s presence, their spatial distributions are expected to be independent of one another. Spatial correlations in their distributions are indicative of interactions and can be modeled by an effective inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 18 publications
1
68
0
Order By: Relevance
“…While the photophysical properties of the probes, labeling and imaging strategies make image analysis complex, with adequate care, it is possible to measure protein stoichiometry (multimeric, dimeric or oligomeric) [43,46], count protein numbers [30,42,44,47,48] and characterize the spatial nano-organization of proteins [33,49]. A number of open-source (typically ImageJ-based) software is now available for biologists who wish to quantify their super-resolution images [24,37]. As the field moves forward, researchers will greatly benefit from the development of new probes or identification of buffer and imaging conditions that lead to high photon outputs, high photoactivation efficiencies and low blinking or re-activation rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the photophysical properties of the probes, labeling and imaging strategies make image analysis complex, with adequate care, it is possible to measure protein stoichiometry (multimeric, dimeric or oligomeric) [43,46], count protein numbers [30,42,44,47,48] and characterize the spatial nano-organization of proteins [33,49]. A number of open-source (typically ImageJ-based) software is now available for biologists who wish to quantify their super-resolution images [24,37]. As the field moves forward, researchers will greatly benefit from the development of new probes or identification of buffer and imaging conditions that lead to high photon outputs, high photoactivation efficiencies and low blinking or re-activation rates.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, multiple appearance of the same probe does not influence the cross-correlation curve, making analysis and interpretation easier. Spatial co-organization and co-localization of proteins can also be quantified by determining an "interaction potential" that is most likely to lead to the observed distribution of point localizations [36,37].…”
Section: Artificial Clustering and Over-countingmentioning
confidence: 99%
“…4B. Identification of EB1 comets in the absence of nucleating sites was done with the MOSAIC plugin (35) for ImageJ. Some images were acquired on the same setup in which the Andor Neo sCMOS camera was used instead.…”
Section: Methodsmentioning
confidence: 99%
“…Because the images in STORM data represent a reconstruction of locations and localization uncertainties of individual molecules, the overlap of signal in images is not the best method for determining whether molecules colocalize. Instead, we used a nearest-neighbor analysis to determine how close each point source is to its nearest neighbor by using the "strength" metric (69,70). Supporting the hypothesis of microdomain mixing, we found that, upon Snx1/2 depletion, the interaction strength between RME-8 and Hrs increased significantly [3.33 (n = 3) compared with 1.13 (n = 3) for control; P < 0.02, t test; Fig.…”
Section: Not All Retromer Associated Proteins Are Important For Domainmentioning
confidence: 99%